تنازع القوانين في عقود التجارة الدولية - أمين مناصف; سامية سعدي (My University, 2019)
Summary The law of will is an original officer in determining the law applicable to international trade contracts in view of its adoption in many international legislation and conventions as well as the jurisprudence of international commercial arbitration, It has also been adopted by Algerian legislation in the text of article 18 of the Algerian Civil Code. of the contract ", but narrowed its scope of application, by stipulating that there must be a genuine link to the contract or contractors. However, the Law of Will has been challenged by many obstacles and exceptions that have been tried without its application, most notably matters of public order, fraud towards law and rules with the necessary application, and we conclude that the Law of Will has been considerably reduced by such exceptions, which may lead to disruption of international trade contracts due to their incompatibility with the expectations and interests of the Contracting Parties ting Parties ting Parties. In the absence of the law of will, the judge's role in determining the law applicable in the international commercial contract is highlighted by its adoption of a rigid attribution or flexible attribution approach, whether on the conventional or electronic international commercial contract. With reference to the Algerian legislature's position under Act No. 18-05 on electronic international commerce, by adopting the rigid approach and restricting its application to the law. ..................... ملخص يعد قانون الارادة ضابط أصلي في تحديد القانون الواجب التطبيق على عقود التجارة الدولية، و ذلك نظرا لتبنيه في العديد من التشريعات و الإتفاقيات الدولية وكذلك قضاء التحكيم التجاري الدولي، و كذلك أخذ به المشرع الجزائري في نص المادة 18 من القانون المدني الجزائري، لكنه ضيق من مجال تطبيقه، من خلال النص على وجوب توافر صلة حقيقية بالعقد أو المتعاقدين. لكن قانون الارادة إعترضته العديد من العراقيل و الاستثناءات التي حاولت دون تطبيقه، أبرزها مسائل النظام العام و الغش نحو القانون و القواعد ذات التطبيق الضروري، و عليه نخلص إلى أن قانون الارادة تراجع كثيرا بسبب هذه الاستثناءات مما قد يؤدي إلى تعطيل عقود التجارة الدولية نظرا لتعارضها مع توقعات و مصالح لأطراف المتعاقدة. أما في حالة غياب قانون الارادة فهنا يبرز دور القاضي في تحديد القانون الواجب التطبيق في العقد التجاري الدولي، بإعتماده على منهج الإسناد الجامدة أو منهج الإسناد المرن سواء كان على العقد التجاري الدولي التقليدي أو الإلكتروني. مع الإشارة لموقف المشرع الجزائري بموجب القانون رقم 18-05 المتعلق بالتجارة الدولية الإلكترونية من خلال إعتماده على المنهج الجامد مع حصر تطبيقه في القانون. ...................... Résumé Le droit du testament est un officier original dans la détermination du droit applicable aux contrats commerciaux internationaux en vue de son adoption dans de nombreuses législations et conventions internationales ainsi que la jurisprudence de l’arbitrage commercial international, Il a également été adopté par la législation algérienne dans le texte de l’article 18 du Code civil algérien. du contrat ", mais a restreint son champ d’application, en stipulant qu’il doit y avoir un lien réel avec le contrat ou les contractants. Cependant, la loi de la volonté a été contestée par de nombreux obstacles et exceptions qui ont été jugés sans son application, notamment des questions d’ordre public, de fraude à la loi et de règles avec l’application nécessaire, et nous concluons que le droit de la volonté a été considérablement réduit par de telles exceptions, qui peuvent entraîner une perturbation des contrats commerciaux internationaux en raison de leur incompatibilité avec les attentes et les intérêts des parties contractantes. En l’absence de la loi du testament, le rôle du juge dans la détermination de la loi applicable dans le contrat commercial international est mis en évidence par son adoption d’une approche d’attribution rigide ou flexible, soit sur le contrat commercial international conventionnel ou électronique. En référence à la position du législateur algérien en vertu de la loi no 18-05 sur le commerce international électronique, en adoptant l’approche rigide et en limitant son application à la loi.